ISSUES AND CHALLENGES IN RECORD MANAGEMENT: THE ADOPTION OF ERMS - Arif Najmi Bin Bahri; Wan Muhammad Iskandar Zulqarnain Bin Wan Jaaffar; Muhammad Hilman Bin Aris; Nur Farahnisa Binti Mohd Azaham; Wan Nor Syazana Wan Hashim (International Journal of Accounting, Finance and Business, 2022)
The purpose of this study is to give a review of the literature on the issues and challenges of the adoption of electronic record management system in an organization. In this review paper, the existing literature on the acceptance of an electronic record management system in organizations is reviewed. Based on the review, this study concluded that both technological and human are the main challenges that need to be concerned on. Human factors include employee’s readiness, training and resistance to change while technological factors involves the challenges from the technological infrastructure and the integration of new technologies. The evaluation will provide future researchers with a comprehensive understanding of the electronic record management system idea and will aid in identifying research gaps. This study will be benefit to the managers or organization in identifying the hindrance factors in ERMS implementation, thus preparing for future strategies in ERMS will be more practical.